Performance evaluation of common rail direct injection (CRDI) engine fuelled with Uppage Oil Methyl Ester (UOME) - D.N. Basavarajappa; N. R. Banapurmath; S.V. Khandal; G. Manavendra (International Journal of Renewable Energy Development, 2015)
For economic and social development of any country energy is one of the most essential requirements. Continuously increasing price of crude petroleum fuels in the present days coupled with alarming emissions and stringent emission regulations has led to growing attention towards use of alternative fuels like vegetable oils, alcoholic and gaseous fuels for diesel engine applications. Use of such fuels can ease the burden on the economy by curtailing the fuel imports. Diesel engines are highly efficient and the main problems associated with them is their high smoke and NOx emissions.  Hence there is an urgent need to promote the use of alternative fuels in place of high speed diesel (HSD) as substitute. India has a large agriculture base that can be used as a feed stock to obtain newer fuel which is renewable and sustainable. Accordingly Uppage oil methyl ester (UOME) biodiesel was selected as an alternative fuel. Use of biodiesels in diesel engines fitted with mechanical fuel injection systems has limitation on the injector opening pressure (300 bar). CRDI system can overcome this drawback by injecting fuel at very high pressures (1500-2500 bar) and is most suitable for biodiesel fuels which are high viscous. This paper presents the performance and emission characteristics of a CRDI diesel engine fuelled with UOME biodiesel at different injection timings and injection pressures. From the experimental evidence it was revealed that UOME biodiesel yielded overall better performance with reduced emissions at retarded injection timing of -10° BTDC in CRDI mode of engine operation.